Indirect Plant Regeneration from Leaf Explants of Mentha piperita (L.) – An Important Multipurpose Medicinal Plant - C.V. Naidu2*, P. Sujana1 and (Journal of Phytology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Peppermint<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> (Mentha piperita) is a hybrid mint, a cross between the watermint (Mentha aquatica) and spearmint (Mentha spicata). The plant, indigenous to Europe, is now widespread in cultivation throughout all regions of the world. Peppermint typically occurs in moist habitats, including stream sides and drainage ditches. Being a hybrid, it is usually sterile, producing no seeds and reproducing only vegetatively, spreading by its rhizomes. If placed, it can grow anywhere, with a few exceptions. <span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">Peppermint is sometimes regarded as the world’s oldest medicine, with archaeological evidence placing its use at least as far back as ten thousand years ago. <span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Callus was obtained on MS media supplemented with different concentrations and combinations of IAA, NAA, BAP, Kn and 2,4-D from leaf explants of Mentha piperita. More number of shoots were differentiated from callus grown on MS medium supplemented with BAP (2mg/l) and further multiplication was achieved by repeatedly sub culturing the nodal segments. About 95% of in vitro shoots developed roots after they were transferred to rooting medium containing IBA (1.5 mg/l). 95% of the plantlets were successfully acclimatized and established in the field.